2017
DOI: 10.1007/s00421-017-3629-6
|View full text |Cite
|
Sign up to set email alerts
|

Oral contraceptive pill use and the susceptibility to markers of exercise-induced muscle damage

Abstract: PurposeFirstly, to establish whether oral contraceptive pill (OCP) users are more susceptible to muscle damage compared to non-users, and secondly, to establish whether differences can be attributed to differences in patella tendon properties.MethodsNine female OCP users and 9 female non-users participated in the investigation. Combining dynamometry, electromyography and ultrasonography, patella tendon properties and vastus lateralis architectural properties were measured pre and during the first of 6 sets of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
28
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(28 citation statements)
references
References 43 publications
0
28
0
Order By: Relevance
“…Collectively, these findings indicate that OCPs might, on average, exert a slightly negative impact on performance, but from a practical point of view the effect magnitude and variability support consideration of an individual's response to OCP use, so that decisions as to the appropriateness of OCP use can be tailored to the individual requirements (e.g., contraceptive or medical need) and response (i.e., to what degree they might be affected) of each athlete. Pooling of data comparing exercise performance between OCP consumption and withdrawal estimated an Anderson et al [35] Grucza et al [46] Grucza et al [47] Elliott et al [5] de Bruyn−Prevost et al [40] Hicks et al [48] Sunderland et al [63] Vaiksaar et al [65] Quinn et al [58] Schaumberg et al [62] Lynch and Nimmo [52] Bushman et al [39] Bell et al [37] Mattu et al [68] Giacomoni et al [22] Gordon et al [45] Drake et al [41] Wirth and Lohman. [66] Minahan et al [55] Bemben et al [38] Isacco et al [49] Sarwar et al [18] Giacomoni and Falgairette [43] Effect size effect that was very close to zero, indicating that exogenous supplementation of oestrogen and progestin is unlikely to have any substantive effect on exercise performance across an OCP cycle.…”
Section: Discussionmentioning
confidence: 99%
“…Collectively, these findings indicate that OCPs might, on average, exert a slightly negative impact on performance, but from a practical point of view the effect magnitude and variability support consideration of an individual's response to OCP use, so that decisions as to the appropriateness of OCP use can be tailored to the individual requirements (e.g., contraceptive or medical need) and response (i.e., to what degree they might be affected) of each athlete. Pooling of data comparing exercise performance between OCP consumption and withdrawal estimated an Anderson et al [35] Grucza et al [46] Grucza et al [47] Elliott et al [5] de Bruyn−Prevost et al [40] Hicks et al [48] Sunderland et al [63] Vaiksaar et al [65] Quinn et al [58] Schaumberg et al [62] Lynch and Nimmo [52] Bushman et al [39] Bell et al [37] Mattu et al [68] Giacomoni et al [22] Gordon et al [45] Drake et al [41] Wirth and Lohman. [66] Minahan et al [55] Bemben et al [38] Isacco et al [49] Sarwar et al [18] Giacomoni and Falgairette [43] Effect size effect that was very close to zero, indicating that exogenous supplementation of oestrogen and progestin is unlikely to have any substantive effect on exercise performance across an OCP cycle.…”
Section: Discussionmentioning
confidence: 99%
“…A few case reports have reported co-trimoxazole as a potential trigger of RML [14,15]. Even though endogenous estrogen appears to attenuate muscle damage in animals, women taking oral contraceptives, thereby having higher exogenous estrogen levels with lower endogenous estrogen levels, appear to be more susceptible to exerciseinduced muscle damage and have an attenuated recovery from exercise-induced muscle damage [16][17][18]. ere are a few case reports of RML developing after administration of diclofenac sodium, but RML following administration of mefenamic acid has not been reported [19][20][21].…”
Section: Discussionmentioning
confidence: 99%
“…In some studies, COC use was reported to increase total and LDL cholesterol [ 30 , 36 , 67 , 379 ], with elevated chronic low-grade inflammation and oxidative stress that could be detrimental to physical activity and elevate cardiovascular risk [ 401 ], such as basal CRP [ 379 , 380 ] alone [ 380 ] or combined with TNFα [ 379 ]. During exercise, an increase in CK [ 402 , 403 ] and a decrease in IL-6 with COCs vs. F was reported in moderate-level athletes [ 350 ], although this was blunted in elite female athletes [ 380 ]. No other cytokine change was found in either temperate or hot conditions [ 381 ], but COC users vs. non-users were reported to have an impaired sweating onset threshold and thermosensitivity [ 404 ].…”
Section: Possible Mechanisms: Performance and Health Risksmentioning
confidence: 99%